BDSM and masochistic sexual fantasies in women with borderline personality disorder: simply on the spectrum of “normality” or source of suffering? - Hannah F. Warkentin; Rose Gholami Mazinan; Johannes Fuss; Leonhard Kratzer; Sarah V. Biedermann (Borderline Personality Disorder and Emotion Dysregulation)
Abstract Background Increasing research has contributed to the destigmatization of sadomasochistic sexual preferences. Nevertheless, persons diagnosed with Borderline Personality Disorder (BPD) frequently report self-harmful masochistic sexual practice under the pretext of BDSM, especially those reporting experiences of child sexual abuse (CSA). Empirical research on sexual preferences in the context of BPD is scarce, although related sexual behaviors may matter particularly regarding dysfunctional and self-harming behaviors. Methods Women with BPD (n = 115) and age-matched healthy controls (HC; n = 115) were compared regarding experiences with BDSM and masochistic fantasies, as well as associated arousal and distress. Regression and moderation analyses were conducted on cross-sectional data to examine the associations between sadomasochistic sexuality and BPD symptoms, traumatic experiences, sexual risk behavior, and sexual motivation. Results Women with BPD practiced BDSM more often (last year: 34% vs. 15%; lifetime: 51% vs. 23%) which was associated with more autonomous, self-determined forms of sexual motivation but at the same time associated with higher BPD symptoms and risky sexuality. While a similar number of women in both groups endorsed arousal through masochistic sexual fantasies (77% vs. 74%), significantly more of those women with BPD reported associated marked distress (53% vs. 21%). Distress from masochistic fantasies was associated with less autonomous sexual motivation, in which sexuality is used in order to regulate emotions and self-esteem, and was predicted by the interaction of the severity of childhood sexual abuse and this regulation tendency. Conclusion Sadomasochistic sexuality and corresponding fantasies in women can be an autonomous, self-determined form of sexuality. However, in women with BPD they tend to be associated with BPD symptoms, risky sexuality, problems with self-regulation and traumatization and are thus associated with marked distress. Our findings highlight the importance of considering sexual preferences in clinical context and the need for specific treatment for this subgroup suffering from their preference or acting them out in a dysfunctional or self-harming way. Trial registration This analysis is part of a larger ongoing study and was retrospectively registered (Registration trial DRKS00029716).